2021
DOI: 10.1007/s11845-021-02594-3
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of burnout and long covid in senior specialist doctors

Abstract: Background Covid-19 has placed unprecedented demand on healthcare systems and on healthcare professionals. There have been concerns about the risk of distress, moral injury and burnout among healthcare professionals, especially doctors. Aim To assess the effect of the ongoing Covid-19 pandemic on Irish doctors by investigating the incidence of burnout and long covid among senior medical staff in Ireland. Methods This is a cross-sectional pilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…However, even if responses are an inaccurate reflection on actual patient contact time, the mismatch between perceived or real service demands and available clinical and administrative support is likely to contribute to high levels of BO. Research already conducted in Ireland during COVID-19, among medical consultants, showed a high prevalence of BO, with three-quarters (n=88) of those screened scoring above cut-offs on the Maslach Burnout Inventory 12…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, even if responses are an inaccurate reflection on actual patient contact time, the mismatch between perceived or real service demands and available clinical and administrative support is likely to contribute to high levels of BO. Research already conducted in Ireland during COVID-19, among medical consultants, showed a high prevalence of BO, with three-quarters (n=88) of those screened scoring above cut-offs on the Maslach Burnout Inventory 12…”
Section: Discussionmentioning
confidence: 95%
“…Research already conducted in Ireland during COVID-19, among medical consultants, showed a high prevalence of Open access BO, with three-quarters (n=88) of those screened scoring above cut-offs on the Maslach Burnout Inventory. 12 Paediatric settings present some unique challenges at a clinical level, in terms of specialised care, a family systems approach, working with a broad multidisciplinary and non-hierarchical team and engagement in high-intensity emotional work. 13 These stressors may have intensified for staff and families during COVID-19, even if not linked to management of actual COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%
“…The experiences reported by senior doctors demonstrate broad-ranging personal and workplace impacts of the pandemic, contributing to worsening mental health. Similarly, a recent study of senior specialist doctors in Ireland reported burnout in 77% of doctors, with 64% experiencing adverse effects on their mental health from the COVID-19 pandemic [ 29 ]. Another study of mental health amongst obstetricians and gynaecologists in the United Kingdom (UK) during the COVID-19 pandemic showed high rates of major depressive disorder and generalised anxiety disorder in both junior and senior doctors [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects on the healthcare industry or sector and their employees have been ignored. The pandemic has created workforce crisis in hospitals all over the world giving rise to a lack of staff and technicians to manage the sudden increase in patient inflow in a difficult situation due to employment leave, the initial inadequacy of personal protective equipment (PPE), supply chain failures, and reduced hospital revenues [ 1 - 3 ]. Health professionals were exposed to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and had to isolate themselves, which was the major factor resulting in an inadequate workforce…”
Section: Introductionmentioning
confidence: 99%